ANALISIS PEMETAAN PERMASALAHAN PEMBUKUAN UMKM DI DAERAH ISTIMEWA YOGYAKARTA - Beni Suhendra Winarso; Indah Kurniawati; Siti Resmi (Optimum: Jurnal Ekonomi dan Pembangunan, 2019)
This study aims to map the condition of MSMEs in the Special Region of Yogyakarta. This study uses MSME respondents in DIY. The selection of respondents was based on the rapid development of MSMEs and was proven to have survived during the monetary crisis and various eruptions and earthquakes. The number of respondents in this study is 65 MSMEs. Data collection is done through questionnaires and direct interviews with respondents. The results of the study show that the MSMEs studied were micro-business groups based on the criteria of the Central Bureau of Statistics and the UMKM Law. Another result of this study is the level of knowledge of MSMEs in terms of accounting is very limited so that the financial statements produced are not in accordance with the standards. A further consequence is that banks doubt financial information made by borrowers. The implication of this research is that the government must educate MSMEs in understanding financial statements. The results of the study in the form of mapping of bookkeeping for MSMEs can be the basis for further research. Research on understanding accounting can be done using experimental methods so that MSMEs can apply research results to their business decision making.